Interpretation of Volatility Tandem Differential Mobility Analyzer (V-TDMA) data for accurate vapor pressure and enthalpy measurement: Operational considerations, multiple charging, and introduction to a new analysis program (TAO). Issue 4 (2nd April 2020) - Oxford, Christopher R.; Dang, Audrey J.; Rapp, Charles M.; Williams, Brent J.
Abstract: Significant evaporation of pure aerosols in a Volatility Tandem Differential Mobility Analyzer (V-TDMA) creates two Condensation Particle Counter (CPC) response peaks. Two hypotheses for the observed peaks have been proposed: the existence of two phases or the separation of the singly charged experimental size distribution from the remaining experimental size distributions with charges greater than 1 (charge separation). To explore this observation, we atomized pure levoglucosan aerosol and evaporated the aerosol until two peaks formed. We used an additional classifier and neutralizer to select particles from each of the two peaks and assessed the number of charges on the particles. The smaller diameter peak contained singly charged particles, and the larger diameter peak contained the remaining charges. The charge separation hypothesis alone accounts for the two-peak observations. We used a new V-TDMA model named TAO and show that charge separation should occur in other pure components as well. The TAO model was then used to display the impact of different DMA transfer functions, different inlet size distributions, and different oven residence time distributions (RTDs) on the CPC response. Large errors are possible when direct measurement of the RTD is not performed or when wide RTDs are used. We recommend use of narrow transfer functions with narrow RTDs to detect charge separation. When the singly charged CPC response is isolated (smaller diameter peak in the two peak response), accurate estimations of vapor pressure can be recovered, assuming accurate values for gas phase diffusivity, surface energy, particle density, etc. are used. Copyright © 2020 American Association for Aerosol Research